Psychometric properties of the Georgian version of Hospital Survey on Patient Safety Culture: a cross-sectional study - Tanja Manser; Nikoloz Gambashidze (BMJ Open)
Objectives To study the psychometric properties of the Georgian version of the Hospital Survey on Patient Safety Culture (HSPSC-GE).Design Cross-sectional study.Setting Three Georgian hospitals.Participants Staff of participating hospitals (n=579 responses, response rate 41.6%).Primary and secondary outcome measures Psychometric properties (Model fit, internal consistency, construct validity) of the instrument, factor structure derived from the data.Results HSPSC-GE demonstrated acceptable construct validity but highly limited internal consistency (Cronbach’s alpha 0.35–0.87). Confirmatory factor analysis with the original 12-factor model resulted in poor model fit (root mean square error of approximation (RMSEA)=0.06; standardised root mean square residuals (SRMR)=0.08; comparative fit index (CFI)=0.74; goodness of fit index (GFI)=0.81; Tucker-Lewis Index (TLI)=0.70). Accounting for reversed item bias resulted in improved fit indices. Exploratory factor analysis resulted in an alternative five-factor model including only 19 items, but with satisfactory model fit (RMSEA=0.07; SRMR=0.07; CFI=0.90; GFI=0.89; TLI=0.88).Conclusions The HSPSC-GE as a whole demonstrated poor psychometric properties. However, a number of dimensions demonstrated acceptable internal consistency and reliability. Our results indicated presence of reversed item bias, which may be inherent to the original instrument design of the HSPSC and should be taken into account while interpreting or comparing results, as well as in analyses of psychometric properties of the instrument. Nevertheless, the HSPSC-GE provides first insights in hospital patient safety culture (PSC) in Georgia and we recommend using it in its full form to facilitate deeper analysis and further development of PSC in Georgian healthcare.